Economic Analysis of Transforaminal Lumbar Interbody Fusion Surgery Utilizing a Curved Bone Removal Device - Peloza, John H.; Millgram, Michael A.; Jacobian, Erel; Kolsky, Daniel E.; Guyer, Richard D.; Le Huec, Jean-Charles; Ashkenazi, Ely (PharmacoEconomics - open, 2021)
Background Transforaminal lumbar interbody fusion (TLIF) represents a commonly performed spinal procedure that poses a significant financial burden on patients, hospitals and insurers. Reducing these costs, while maintaining efficacy, may be assisted by a new powered endplate preparation device, designed to shorten procedural time while offering positive impacts on other elements that contribute to the cost of care. Objective The aim of the study was to assess and compare the individual cost elements of TLIF procedures with and without the use of the device, to determine whether application of this technology translated into any material procedural savings. Methods The records of 208 single-level TLIF procedures in a single hospital were reviewed. Surgical time, length of hospital stay, blood loss, infection rate, and other parameters were compared for the cases where the device was used (device group; n = 143) and cases which used standard tools (control group; n = 65). The cost per unit of each element was derived from the literature, online resources, and the hospital’s financial department. Results The analysis revealed a shorter surgery duration in the device group (23 min, after controlling for procedure year and patient characteristics; statistically significant at p < 0.001) and lower complication and readmission rates ( p = 0.67 and p = 0.21, respectively) associated with the use of the device, leading to a statistically significant cost reduction of approximately 2060 US dollars (US$) ( p < 0.01). Conclusion The study suggests that use of the device may lead to a cost reduction and shorter procedure without deteriorating the clinical outcome.